Study of vascular segments of the kidney by vascular injection method - A Martin Lucas; Sanjay Joseph Fernandes; Pranup Roshan Quadras; R Roshni Benedicta (Wolters Kluwer Medknow Publications, 2017)
Background & aims : Kidneys are the main excretory organs in our body. About one-fifth of the total cardiac output is supplied to the kidneys via renal arteries. This study focusses on renal artery branching pattern which is very useful for various surgical procedures. This study is done by taking a cast of vascular segments of kidney by injecting a silicone rubber into the renal arteries using RTV 116 silicone rubber. Materials and methods : Kidney specimens from well embalmed cadavers were taken and a flowable silicone rubber is injected into the renal arteries via a cannula. Then the arteries were ligated and kept aside to solidify. Next step was to bring about degradation of the kidney tissue to leave behind the silicone rubber residue of the branching pattern by immersing the organ in KOH solution. Result: Branching pattern was observed and documented in all 20 specimens. Conclusion: Knowledge of the branching pattern of renal artery is instrumental in surgeries for it to be a success and more so in renal transplants. Thus, this study would help to provide a better picture of vascularization of the kidney along with its segmental pattern.